PRINCIPLE OF ISLAMIC BASED LESSON PLANNING: PRINCIPLE OF ISLAMIC BASED LESSON PLANNING - Hasibuan, Kalayo; Saftari, Anggri; Mufida Azzahro, Azizah; Lestari, Azlin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic-based lesson planning is an educational approach that integrates Islamic values into all components of learning, including objectives, materials, methods, learning activities, and assessment. This article aims to examine the main principles, benefits, and challenges of implementing Islamic-based lesson planning through a critical narrative literature review. The data were collected from various academic sources published between 2015 and 2025 and analyzed using a thematic analysis approach. The findings reveal four major principles of Islamic-based lesson planning: Tawhid-based orientation, integration of Islamic values into instructional design, character (akhlaq) formation as an educational goal, and contextual as well as adaptive pedagogy. Furthermore, Islamic- based lesson planning contributes positively to students’ academic, moral, spiritual, and social development through the integration of values such as honesty, discipline, responsibility, and social awareness in the learning process. However, its implementation still faces several challenges, including teachers’ limited understanding, insufficient professional training, limited instructional resources, and difficulties in systematically integrating Islamic values across different subjects. Therefore, stronger institutional support, teacher professional development, and more structured implementation frameworks are needed to ensure the successful application of Islamic-based lesson planning.